Eocene maar sediments record warming of up to 3.5 °C during a hyperthermal event 47.2 million years ago - Schmitt, Clemens; Vasiliev, Iuliana; Meijer, Niels; Brugger, Julia; Kaboth-Bahr, Stefanie; Bahr, André; Mulch, Andreas (Communications earth & environment, 2024)
Eocene hyperthermal events reflect profound perturbations of the global carbon cycle. Most of our knowledge about their onset, timing, and rates originates from marine records. Hence, the pacing and magnitude of hyperthermal continental warming remains largely unaccounted for due to a lack of high-resolution climate records. Here we use terrestrial biomarkers and carbon isotopes retrieved from varved lake deposits of the UNESCO World Heritage site ‘Messel Fossil Pit’ (Germany) to quantify sub-millennial to millennial-scale temperature and carbon isotope changes across hyperthermal event C21n-H1 (47.2 million years ago). Our results show maximum warming of ca. 3.5 °C during C21n-H1. We propose that two components are responsible for the warming pattern across the hyperthermal: (1) the massive release of greenhouse gases into the atmosphere-ocean system and (2) half-precession orbital forcing indicated by ~12.000-year temperature cycles. The carbon isotope record of bulk organic matter indicates a sharp, 7‰ decrease at the peak of the hyperthermal, corresponding to increased organic carbon content and a shift in the lake algal community. Collectively, our proxy data reveal the structure of continental temperature response during the hyperthermal event that is characterized by overall warming with a superimposed pattern of sub-orbital scale temperature fluctuations.
Gesehen am 10.10.2024